The Other Russia Local experience and societal change - Granberg, Leo (Taylor & Francis, 2016)
Most recent research seeks to explain contemporary changes in Russia by analysing the decisions of Russian leaders, oligarchs and politicians based in Moscow. This book examines another Russia, one of ordinary people changing their environment and taking opportunities to provoke societal changes in small towns and the countryside. Russia is a resource-rich society and the country's strategy and institutional structure are built on the most valuable of these resources: oil and gas. Analysing the implications of this situation at the local level, this book offers chapters on resource use, local authorities, enterprises, poverty and types of individual, as well as a final chapter which places local societies within the framework of the Russian politicised economy. Based on extensive empirical data gathered through more than 400 semi-structured interviews with entrepreneurs, teachers, social workers and those working for the local authorities, this book sheds light on the role of local activity in the development of Russian society and is essential reading for students and scholars interested in Russia and its politics.